Is transcranial direct current stimulation beneficial for treating pain, depression, and anxiety symptoms in patients with chronic pain? A systematic review and meta-analysis - Wen, Yu-Rong; Shi, Jian; Hu, Zheng-Yu; Lin, Yang-Yang; Lin, You-Tian; Jiang, Xue; Wang, Rui; Wang, Xue-Qiang; Wang, Yu-Ling (Frontiers in Molecular Neuroscience, 2022)
Background Chronic pain is often accompanied by emotional dysfunction. Transcranial direct current stimulation (tDCS) has been used for reducing pain, depressive and anxiety symptoms in chronic pain patients, but its therapeutic effect remains unknown. Objectives To ascertain the treatment effect of tDCS on pain, depression, and anxiety symptoms of patients suffering from chronic pain, and potential factors that modulate the effectiveness of tDCS. Methods Literature search was performed on PubMed, Embase, Web of Science, and Cochrane Library from inception to July 2022. Randomized controlled trials that reported the effects of tDCS on pain and depression and anxiety symptoms in patients with chronic pain were included. Results Twenty-two studies were included in this review. Overall pooled results indicated that the use of tDCS can effectively alleviate short-term pain intensity [standard mean difference (SMD): −0.43, 95% confidence interval (CI): −0.75 to −0.12, P = 0.007] and depressive symptoms (SMD: −0.31, 95% CI, −0.47 to −0.14, P < 0.001), middle-term depressive symptoms (SMD: −0.35, 95% CI: −0.58 to −0.11, P = 0.004), long-term depressive symptoms (ES: −0.38, 95% CI: −0.64 to −0.13, P = 0.003) and anxiety symptoms (SMD: −0.26, 95% CI: −0.51 to −0.02, P = 0.03) compared with the control group. Conclusion tDCS may be an effective short-term treatment for the improvement of pain intensity and concomitant depression and anxiety symptoms in chronic pain patients. Stimulation site, stimulation frequency, and type of chronic pain were significant influence factors for the therapeutic effect of tDCS. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=297693, identifier: CRD42022297693.